Pengaruh Kesadaran Wajib Pajak, Digitalisasi Perbankan dan Kualitas Pelayanan On-Site terhadap Kepatuhan Pembayaran Pajak Bumi dan Bangunan Tahun 2021 (Studi Kasus di Kecamatan Sawangan, Kota Depok) - Ambarwati Ambarwati; Dicky Anugrah Afriyansyah (Jurnal Pajak Vokasi (JUPASI), 2023)
The National Development Planning Agency estimates that Indonesia has a population of 267 million people and is an archipelagic nation. Due to its large population, Indonesia works hard to ensure that all citizens benefit from fair and comprehensive national developmentTherefore, to cover the required budget, the government uses state revenues as a source of funds. State revenues are all state revenues originating from tax revenues, non-tax state revenues, and grants, according to Law Number 17 of 2003 concerning state finances. The City Government of Depok has made innovations by using technological facilities to make it easier for taxpayers to obtain information regarding land and buildingtaxes and to conduct transactions regarding land and building taxes. After that, another basic factor that must be considered in influencing taxpayers to comply with tax payments is the quality of service (on-site). The population in this study is 207,435 taxpayers in Sawangan District, Depok City (KPP Sawangan, 2021). Determining the number of samples in this study using the Slovin formula resulted in as many as 417 taxpayers. The methods used for data collection are questionnaires and documentation. The data analysis technique used is multiple regression. The results of the study show that taxpayer awareness, banking digitization, and service quality affect taxpayer compliance in paying PBB in Sawangan District and Depok City in 2021, both partially and simultaneously. Thus, the city government of Depok should make efforts to increase awareness of taxpayers paying PBB by intensifying socialization, counseling, and providing knowledgeand understanding related to this awareness, improving the quality of tax services, and making it easier for taxpayers to pay the United Nations.